Friction and Wear Behaviors of Surface-Modified Carbon Fabric/Epoxy Resin Composites. Issue 5 (4th May 2019) - Xue, Feng; Su, Chao; Li, TongSheng
Abstract: Carbon fabric (CF) was pretreated by air-plasma bombardment and then further modified by deposition of polydopamine on the surface of the pretreated CF. Epoxy resin composites reinforced by unmodified or surface-modified carbon fabric were fabricated. The friction and wear behaviors of the resulting composites were evaluated in a ring-on-block contact mode. The flexural strength and Rockwell hardness of the composites were also evaluated. The morphologies of the worn surfaces of the unmodified and modified composites were analyzed by scanning electron microscopy. The surface treatment increased the surface roughness and changed the surface topography of the CF, which contributed to enhancing the interfacial adhesion of the composites and thus improved the mechanical properties and tribo-performance. The friction and wear properties of both the unfilled and filled composites were highly dependent on the load and sliding velocity. Moreover, the results were supplemented with scanning electron micrographs to help understand the possible wear mechanisms.